Primary Ciliary Dyskinesia - Lobo, Jason; Zariwala, Maimoona A.; Noone, Peadar G. (Seminars in Respiratory and Critical Care Medicine, 2015)
Primary ciliary dyskinesia (PCD) is an autosomal recessive disorder of cilia structure, function, and biogenesis leading to chronic infections of the respiratory tract, fertility problems, and disorders of organ laterality. The diagnosis can be challenging, using traditional tools such as characteristic clinical features, ciliary function, and ultrastructural defects and newer screening tools such as nasal nitric oxide levels and genetic testing add to the diagnostic algorithm. There are 32 known PCD-causing genes, and in the future, comprehensive genetic testing may screen young infants before developing symptoms, thus improving survival. Therapies include surveillance of pulmonary function and microbiology, in addition to airway clearance, antibiotics, and early referral to bronchiectasis centers. As with cystic fibrosis (CF), standardized care at specialized centers using a multidisciplinary approach likely improves outcomes. In conjunction with the CF foundation, the PCD foundation, with experienced investigators and clinicians, is developing a network of PCD clinical centers to coordinate the effort in North America and Europe. As the network grows, clinical care and knowledge will improve.
Keywords: bronchiectasis; cilia; ciliary dyskinesia; sinusitis; otitis; dynein arms; situs inversus; Pseudomonas aeruginosa